Geranylgeranylacetone Ameliorates Beta-Amyloid Toxicity and Extends Lifespan via the Heat Shock Response in Caenorhabditis elegans - Mossiah, Isiah; Perez, Sabrina M.; Stanley, Taylor R.; Foley, Michaela K.; Kim Guisbert, Karen S.; Guisbert, Eric (Frontiers in Aging, 2022)
Activation of a cytoprotective cellular pathway known as the heat shock response (HSR) is a promising strategy for the treatment of Alzheimer’s disease and other neurodegenerative diseases. Geranylgeranylacetone (GGA) is a commonly used anti-ulcer drug in Japan that has been shown to activate the HSR. Here, we establish C. elegans as a model system to investigate the effects of GGA. First, we show that GGA-mediated activation of the HSR is conserved in worms. Then, we show that GGA can ameliorate beta-amyloid toxicity in both muscle and neuronal worm Alzheimer’s disease models. Finally, we find that exposure to GGA is sufficient to extend the lifespan of wild-type worms. Significantly, the beneficial effects of GGA on both beta-amyloid toxicity and lifespan are dependent on HSR activation. Taken together, this research supports further development of GGA as a therapeutic for Alzheimer’s disease, provides evidence that HSR activation is a relevant therapeutic mechanism, and indicates that the beneficial effects of GGA are not limited to disease.